Interreligious Environmentalism: The Way Ahmadiyya Group Engages to Interfaith Dialogue - Khalil Muflih, Miftha (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2023)
There have been many studies on Ahmadiyya and their involvement in inter/intra-religious dialogue. However, some of these studies only look at how the dialogue takes shape or tends to be formal. Ahmadiyya, which is a vulnerable religious group, certainly needs a new model of dialogue or encounter. This article assumes that